The Cost of an Upper Gastroduodenal Endoscopy: An Activity-Based Approach. (2002) - Crott, Ralph; Makris, Nicholaos; Barkun, Alan; Fallone, Carlo
Abstract : The cost of medical procedures is often unknown, but is nevertheless crucial for setting reimbursement and health care policies. The cost of an upper gastroduodenal endoscopy was investigated in ambulatory adults in a large academic hospital in the province of Quebec, from the perspective of the hospital. An activity-based costing methodology was used to break down the procedure into a number of priory tasks, to which resources used at the department level (labour, equipment, materials) were allocated. The direct cost of performing an endoscopy ranged from 62 for an unsedated, unbiopsied patient to 89 for a sedated, biopsied patient. Not included in this amount were separate reimbursement fees of 15 for biopsy analysis and the 50 professional fee for the performing physician, which are charged directly to the Ministry of Health. Incorporating overall, general hospital fixed overhead costs raises the cost of the procedure substantially, by 41, as does the use of nonreusable biopsy forceps, which adds about 63 to the total cost of the procedure. Given the high proportion of overall, hospital-wide, overhead costs in the total cost of the procedure, allocation methods of these overhead costs in current hospital accounting systems should be improved to obtain a more precise estimate of the full cost of upper gastroduodenal endoscopy.